Parliamentary versus presidential government - Lijphart, Arend (Oxford Oxford University Press, 1992)
Parliamentary and presidential governments--exemplified by most European countries for the former and the United States and Latin America for the latter--are the two principal forms of democracy in the modern world. Their respective advantages and disadvantages have been long debated, at first mainly by British and American political observers but with increasing frequency in other parts of the world, especially in Latin America, but also in Western and Eastern Europe and Asia. The recent world-wide wave of democratization has intensified both the debate and its significance. This volume brings together the most important statement on the subject by advocates and analysts--from Montesquieu and Madison to Lipset and Linz. It also treats the merits of less frequently used democratic types, such as French-style semi-presidentialism, that may be regarded as intermediate forms between parliamentarism and presidentialism.
Prepublication Record
Keywords: Comparative government